2016
DOI: 10.1038/srep26157
|View full text |Cite
|
Sign up to set email alerts
|

CXCR6 marks a novel subset of T-betloEomeshi natural killer cells residing in human liver

Abstract: Natural killer cells (NK) are highly enriched in the human liver, where they can regulate immunity and immunopathology. We probed them for a liver-resident subset, distinct from conventional bone-marrow-derived NK. CXCR6+ NK were strikingly enriched in healthy and diseased liver compared to blood (p < 0.0001). Human hepatic CXCR6+ NK had an immature phenotype (predominantly CD56brightCD16−CD57−), and expressed the tissue-residency marker CD69. CXCR6+ NK produced fewer cytotoxic mediators and pro-inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
296
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 204 publications
(341 citation statements)
references
References 30 publications
43
296
2
Order By: Relevance
“…When looking at education in the context of NKG2A and its ubiquitously present educating HLA-E ligand, both mixed and single reconstituted huNSG mice showed equal education, consistent with invariant HLA-E expression by all HFL donors ( Figure 4D). Additionally, we could also show that education was detectable in the livers of huNSG mice, albeit at decreased overall degranulation capacity, consistent with the findings of previous studies (38,39). Therefore, human NK cell education takes place in huNSG mice, independently of EBV infection, is mediated by the hematopoietic compartment, and is reliant on the presence of cognate HLA on all hematopoietic cells.…”
Section: Ebv Infection Does Not Force Skewing Of the Kir Repertoire Osupporting
confidence: 79%
“…When looking at education in the context of NKG2A and its ubiquitously present educating HLA-E ligand, both mixed and single reconstituted huNSG mice showed equal education, consistent with invariant HLA-E expression by all HFL donors ( Figure 4D). Additionally, we could also show that education was detectable in the livers of huNSG mice, albeit at decreased overall degranulation capacity, consistent with the findings of previous studies (38,39). Therefore, human NK cell education takes place in huNSG mice, independently of EBV infection, is mediated by the hematopoietic compartment, and is reliant on the presence of cognate HLA on all hematopoietic cells.…”
Section: Ebv Infection Does Not Force Skewing Of the Kir Repertoire Osupporting
confidence: 79%
“…In contrast to the mouse, both T-bet and Eomes expression is evident in human fetal NK cells ( The pattern of Eomes and T-bet staining recapitulates what has been shown in adult human liver samples (18,19), where a distinct population of Eomes hi T-bet lo cells has been identified. This Eomes hi population is described as coexpressing CXCR6 and CD69 as markers of tissue residency, with reports differing on whether the Eomes hi cells are more or less cytotoxic than peripheral blood T-bet hi NK cells (18,19,25). A similar CXCR6 + CD69 + population is also described in human lymphoid tissue (26), although the relative expression of Eomes and T-bet was not examined.…”
Section: Cd94mentioning
confidence: 81%
“…Murine T-bet-dependent hILC1s are enriched in liver and other mucosal organs and are the predominant ILC1 population found in the neonate, whereas postnatal expression of Eomes directs differentiation of the cILC1 subset, which increases in frequency as neonatal pups reach weaning and young adulthood (15,17). In contrast, recent studies have demonstrated that tissue-resident NK cells in the human are Eomes + , while the majority of circulating NK cells are T-bet + (18,19). Whether there is also differential distribution of Eomes + and T-bet + NK cells according to age in the human remains to be established.…”
Section: Introductionmentioning
confidence: 78%
“…More recently, trNK cell populations have also been described in human BM, spleen, lung, and liver (Aw Yeang et al, 2017; Cuff et al, 2016; Hudspeth et al, 2016; Lugthart et al, 2016; Lunemann et al, 2013; Marquardt et al, 2015; Marquardt et al, 2017; Stegmann et al, 2016). These various populations of human trNK cells described to date share a number of common features with each other and are overall quite distinct from PB CD56 bright cNK cells (Melsen et al, 2016).…”
Section: Non-conventional Nk Cells In Human Tissues: Specialized Trnkmentioning
confidence: 99%
“…In addition, trNK cells express CCR5, the receptor for CCL3, CCL4, and CCL3L1, as well as CXCR6, the receptor for CXCL16. CD103 (integrin α E ), which binds E-cadherin, is also preferentially expressed by trNK cells in tissues such as MALTs that have an epithelial component (Cuff et al, 2016; Hudspeth et al, 2016; Lugthart et al, 2016; Stegmann et al, 2016). In addition to the above, whereas most PB CD56 bright and CD56 dim cNK cells express CD49e (integrin α 5 ), the absence of this surface protein appears to specifically identify trNK cells, at least in human liver (Aw Yeang et al, 2017).…”
Section: Non-conventional Nk Cells In Human Tissues: Specialized Trnkmentioning
confidence: 99%